59 years old male with local advanced adenoid cystic carcinoma of the hypopharynx – A case report and a review of the literature. (February 2018) - Muhammed, Amr; Mohamed, Ahmed; Elnakib, Esraa; Omar, Amal; Elnakib, Nahawand
Highlights: Review of literature of pharyngolaryngeal minor salivary gland tumour. Illustrate a case with a rare presentation of adenoid cystic carcinoma. Discuss the obstacles and limitation in the treatment of the disease. Abstract: Minor Salivary Gland tumours are rare, representing 2% of the head and neck tumours and less than 1% of hypopharyngeal cancers. The most common subtype of minor salivary gland tumours is adenoid cystic carcinoma. Although there are several case reports discussed it, there are only two reports discussing hypopharyngeal presentation in the literature, and they were treated by surgical resection. Despite that, our case report still to be unique as it presents a case of irresectable locally advanced tumour subjected to a trial of induction therapy.